The Dangers of Unregulated Economic Ideologies in Indonesia and Kazakhstan: Lessons from the Timah and Kazatomprom Cases - Siahaan, Rio Andre Winter; Meliala, Aurora Jillena; Akhmetova, Assem (Faculty of Law, Universitas Tanjungpura, 2025)
AbstractEconomic ideology plays a crucial role in shaping a country